Jerzy Hamerski – twórca poznańskiej pedagogiki „łejerskiej” - Sadowska, Katarzyna (Studia Edukacyjne, 2026)
This study aims to present the profile and pedagogical concept of Jerzy Hamerski, the founder of the Poznań “Łejery” school. A review of existing and elicited sources made use of content analysis. The existing sources include scientific articles, “Łejery” publications, websites related to “Łejery” that contain press releases, and other relevant sources. Elicited sources include interviews conducted with J. Hamerski at Primary School No. 83 in the 2023/2024 school year. Additionally, participant observation conducted by the author in the 2023/2024 and 2024/2025 school years focused on the analysis of the social and physical spaces of Primary School No. 83 in Poznań and the implementation of the “Łejery” pedagogy concept. Thanks to the non-standard solutions initiated and developed by J. Hamerski, the concept of “Łejery pedagogy” established in 1975 and the Emilia Waśniowska Primary School No. 83 in Poznań, established by Hamerski and Elżbieta Drygas (in 1990), remains an open concept, modified depending on the challenges of the modern world observed by teachers and parents. Children win the highest awards in inter-subject competitions and international competitions, learning in a favorable educational space.